La gallinita roja y la espiga de trigo - Finch, Mary; Bell, Elisabeth (Cambridge, MA : Barefoot Books, 2001)
A retelling of the traditional tale of the little red hen whose lazy friends are unwilling to help her plant, harvest, or grind the wheat into flour, but are willing to help her eat the bread she makes from it. In this version, the story continues with her later finding a second grain and everyone willing to help her. Includes a recipe for whole wheat bread written in Spanish.
Accelerated Reader
Keywords: Chickens -- Juvenile literature; Bread -- Juvenile literature; Spanish language materials -- Juvenile literature; Folklore